Events and the environment - Case, Robert (Routledge, 2013)
"Many of our planet's support systems are in crisis. Climate change, resource shortages and environmental pollution threaten our economy and lifestyles. Society as a whole needs to adopt policies that can meet these challenges. The ever expanding event industry is no exception. Anyone involved in organising and managing events needs to understand the complex relationship between events and the environment so that they can implement sustainable management practices. This is the first book to provide a thorough exploration of the multi-dimensional relationships between events and the environment. It achieves this by not only critically evaluating the positive and negative impacts on the environment but also by reviewing the ways the events industry uses the environment as a resource and how the environment helps to shape events. It traces the evolution of the concepts of sustainability and sustainable development and the implementation of environmental legislation. It offers insights into how sustainable measurement practices can be incorporated into the planning, management and monitoring of events and concludes by reflecting on some of the future environmental issues that still need to be resolved within the industry. It illustrates these ideas with a wide range of case studies at a variety of scales and geographical locations on all the earth's continents. To encourage reflection on the principal themes and promote critical thinking, there are discussion questions and links to further reading in each chapter. This book is essential reading for students of Events Management."--Publisher's website.